Melawan Korupsi dari Bawah: Strategi Penguatan Akuntabilitas Lokal dalam Pengelolaan Keuangan Desa - Nurjaman, Rusman (P2KK LIPI, 2018)
The mechanism of transparency and accountability of village financial management is currently more regulated within technical implementation regulations that are vertical. It is seen from the regulation that require accountability for village financial management to be addressed to local and central government. However, in practice the vertical accountability approach is considered ineffective. The multilayered arrangements and tight controls through the supervision of many supra-village actors are in fact only powerful in curbing and dictating the village, rather than establishing them. In contrast, corruption practices in rural areas are increasingly widespread with increasing funds being channeled to the villages through fund transfer schemes from APBN for villages or Dana Desa. This paper has two purposes. First, it shows weakness and at the same time criticizes the dominance of vertical transparency and accountability mechanisms in village financial management. Secondly, it offers a strategy for strengthening local accountability as an alternative to fighting corruption from below - with and by the village community itself as its main actor - in managing village finances. The supervisory model built up, in addition to not ensuring the village budget management is free from elite capture, also gives space to rent-seeking networks in the regions and villages. This paper offers a strategy of strengthening local village accountability as an alternative solution to get out of the corruption crisis in the village. Strengthening local accountability among others can be done through empowerment approach and institutionalization of democracy by strengthening existing channels and working in village communitarian democracy schemes, namely through strengthening BPD, strengthening village meetings, building citizen forums, building village information systems, and designing systems or citizen complaints mechanism. Kata Kunci: pengelolaan keuangan desa, partisipasi, akuntabilitas lokal, demokrasi komunitarian.